2017
DOI: 10.1080/00365513.2017.1379090
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and cancer

Abstract: Subclinical vitamin K deficits refer to carboxylation defects of different types of vitamin K-dependent hepatic and extrahepatic so-called Gla proteins without prolongation of the prothrombin time. This condition has been reported in different clinical situations due to insufficient supply or malabsorption of vitamin K as well as drug interactions. This review discusses the effects of different vitamin K subspecies on tumour growth and the possible anti-tumour effects of increased vitamin K intake. Blocking ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 131 publications
0
29
0
2
Order By: Relevance
“…Additionally, it is known that PIVKA-II is produced by the liver not only in presence of neoplastic cells, but also in absence of vitamin K ( 12 ). Various in vitro and in vivo studies have demonstrated anti-carcinogenic effects played by vitamin K both directly (due to its ability to suppress cancer growth and cause apoptosis in neoplastic cells) and indirectly through post-translational activation of proteins including PIVKA-II, which have thus been proposed as tumour markers for diverse types of malignancies ( 10 ). According to these findings, the hypothetical mechanism we speculate for PIVKA-II high concentrations in PC is that they could reflect a possible association between vitamin K status and PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is known that PIVKA-II is produced by the liver not only in presence of neoplastic cells, but also in absence of vitamin K ( 12 ). Various in vitro and in vivo studies have demonstrated anti-carcinogenic effects played by vitamin K both directly (due to its ability to suppress cancer growth and cause apoptosis in neoplastic cells) and indirectly through post-translational activation of proteins including PIVKA-II, which have thus been proposed as tumour markers for diverse types of malignancies ( 10 ). According to these findings, the hypothetical mechanism we speculate for PIVKA-II high concentrations in PC is that they could reflect a possible association between vitamin K status and PC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rising attention has been focusing on the relationship between vitamin K and malignancy. Regarding PC, multiple studies have confirmed that apoptosis has a key role in vitamin K-induced pancreatic cell death and the contribution of vitamin K against PC cell oncogenesis has been recently evaluated, with all studies having the common topic of apoptosis ( 10 , 11 ). In the light of these recent articles, we decided to investigate the role of prothrombin induced by vitamin K absence II (PIVKA-II).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen patients had different types of cancer. The prolonged suboptimal function of Gla proteins can increase the risk of cancer, as suggested by studies where vitamin K intake was inversely correlated to cancer incidence [ 28 , 29 ], as well as by the documented anti-carcinogenic effects of vitamin K [ 30 ]. The expression of MGP has been investigated in several cancer types, but no clear role has been established [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K2 administration in vivo inhibits the cellular proliferation of several types of cancers [ 72 , 73 ]. Many studies investigated the role of vitamin K intake and supplementation in the prevention of cancer development, progression, and recurrence [ 74 ].…”
Section: Vitamin K a Family Of Vitamers: Types Status And Vitammentioning
confidence: 99%